2010
DOI: 10.1111/j.1467-7687.2010.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Deaf and hearing children: a comparison of peripheral vision development

Abstract: This study investigated peripheral vision (at least 30° eccentric to fixation) development in profoundly deaf children without cochlear implantation, and compared this to age-matched hearing controls as well as to deaf and hearing adult data. Deaf and hearing children between the ages of 5 and 15 years were assessed using a new, specifically paediatric designed method of static perimetry. The deaf group (N = 25) were 14 females and 11 males, mean age 9.92 years (range 5-15 years). The hearing group (N = 64) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 66 publications
(93 reference statements)
4
43
0
Order By: Relevance
“…Maturation of peripheral vision has been reported to occur as young as 5 years 2 and as old as 13 years of age, 3 with a range of peripheral vision maturities reported between these ages. [4][5][6][7][8][9][10][11] These vast maturity differences likely result from hugely different perimetric methods. For example, 20 eccentricity was used by Blumenthal et al 8 and over 90 eccentricity by other studies.…”
Section: Introductionmentioning
confidence: 99%
“…Maturation of peripheral vision has been reported to occur as young as 5 years 2 and as old as 13 years of age, 3 with a range of peripheral vision maturities reported between these ages. [4][5][6][7][8][9][10][11] These vast maturity differences likely result from hugely different perimetric methods. For example, 20 eccentricity was used by Blumenthal et al 8 and over 90 eccentricity by other studies.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at data from the children, this deaf advantage was only apparent from the age of 11 years onwards – prior to that there was no observed difference between the groups. A subsequent report by Codina, Buckley, Port, and Pascalis (2011) looked at how accurately 5–15 year old deaf and hearing children could detect LED lights in the far periphery (30–85 degrees of visual angle). They reported that deaf children outperformed hearing children in the 13–15 year age category.…”
Section: Introductionmentioning
confidence: 99%
“…When faces are inverted, hearing participants can only rely on their central regions of attention due to the contraction of the "perceptual field" and, therefore, when they were attending to the eye (mouth) region of the inverted faces, they were not able to detect changes in the mouth (eye) region in their peripheral region of attention. Deaf participants, however, due to the sign language experience, possessed greater attentional resources in the periphery visual field as compared to hearing participants (Armstrong et al, 2002;Bavelier et al, 2000Bavelier et al, , 2006Bosworth & Dobkins, 2002;Buckley et al, 2010;Codina et al, 2011;Dye et al, 2009;Lore & Song, 1991;Neville & Lawson, 1987;Proksch & Bavelier, 2002;Stivalet et al, 1998). Therefore, when processing inverted faces, although the "perceptual field" was also smaller as compared to when processing upright faces, deaf participants were still able to utilize some of the peripheral visual field attentional resources to detect the changes.…”
Section: Discussionmentioning
confidence: 76%
“…There is evidence showing that the deprivation of auditory input can result in the redistribution of attentional resources across the visual field. For example, several studies showed that deaf participants had enhanced attention to the information at their peripheral visual field, but possessed less attentional resource at their centre visual field as compared to the hearing controls (Armstrong, Neville, Hillyard, & Mitchell, 2002;Bavelier et al, 2000Bavelier et al, , 2006Bosworth & Dobkins, 2002;Buckley, Codina, Bhardwaj, & Pascalis, 2010;Codina, Buckley, Port, & Pascalis, 2011;Dye, Hauser, & Bavelier, 2009;Lore & Song, 1991;Neville & Lawson, 1987;Proksch & Bavelier, 2002;Stivalet, Moreno, Richard, Barraud, & Raphel, 1998; see Bavelier & Neville, 2002;Bavelier, Dye, & Hauser, 2006, for reviews). This cross-channel compensation effect was consistent with the findings using neural-imaging methods that enhanced activities in the auditory cortex were observed when processing visual information for deaf participants as compared to the hearing controls (for a review, see Bavelier & Neville, 2002).…”
mentioning
confidence: 96%